Numerical modelling of hydrodynamics and tidal energy extraction in the Alderney Race: a review. (21st August 2020) - Thiébot, Jérôme; Coles, D. S.; Bennis, Anne-Claire; Guillou, Nicolas; Neill, Simon; Guillou, Sylvain; Piggott, Matthew
Abstract : The tides are a predictable, renewable, source of energy that, if harnessed, can provide significant levels of electricity generation. The Alderney Race (AR), with current speeds that exceed 5 m s −1 during spring tides, is one of the most concentrated regions of tidal energy in the world, with the upper-bound resource estimated at 5.1 GW. Owing to its significance, the AR is frequently used for model case studies of tidal energy conversion, and here we review these model applications and outcomes. We examine a range of temporal and spatial modelling scales, from regional models applied to resource assessment and characterization, to more detailed models that include energy extraction and array optimization. We also examine a range of physical processes that influence the tidal energy resource, including the role of waves and turbulence in tidal energy resource assessment and loadings on turbines. The review discusses model validation, and covers a range of numerical modelling approaches, from two-dimensional to three-dimensional tidal models, two-way coupled wave-tide models, Large Eddy Simulation (LES) models, and the application of optimization techniques. The review contains guidance on model approaches and sources of data that can be used for future studies of the AR, or translated to other tidal energy regions. This article is part of the theme issue 'New insights on tidal dynamics and tidal energy harvesting in the Alderney Race'.